Strategi Promosi Kesehatan Pencegahan Stunting di Puskesmas Muara Bulian Kabupaten Batang Hari - Pangga, Kiki Kurnia; Budiyanto, M. Nur (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research is to examine health promotion strategies for preventing stunting at the Muara Bulian Community Health Center, Batang Hari Regency. The research method used is a qualitative descriptive method. The 5 (five) strategies applied in this research are the Ottawa Charter (1986), namely a supportive environment, policies with a health perspective, community movements, individual abilities/skills, and reorientation of health sector services. The results of this research prove that in implementing health promotion strategies, there are still obstacles in the form of the community not being fully participatory in participating in health activities as organized by the health promotion staff at the Muara Bulian Community Health Center, Batang Hari Regency.